2009
DOI: 10.1096/fj.08-121624
|View full text |Cite
|
Sign up to set email alerts
|

PPARα and PPARγ attenuate HIV‐induced dysrégulation of tight junction proteins by modulations of matrix metalloproteinase and proteasome activities

Abstract: The blood-brain barrier (BBB) plays an important role in HIV trafficking into the brain and the development of the central nervous system complications in HIV infection. Tight junctions are the main structural and functional elements that regulate the BBB integrity. Exposure of human brain microvascular endothelial cells (hCMEC/D3 cell line) to HIV-infected monocytes resulted in decreased expression of tight junction proteins, such as junctional adhesion molecule-A (JAM)-A, occludin, and zonula occludens (ZO)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 67 publications
(89 reference statements)
5
95
1
Order By: Relevance
“…1A, and 2, A and B). These are molecular mass reported previously for the two proteins (Szatmari et al, 2006;Huang et al, 2009). We observed some interindividual differences in BCRP and to a lesser extent PPAR␣ expression in BBB-ECs (Fig.…”
Section: Expression Of Bcrp and Ppar␣ Proteins In Hcmec/d3supporting
confidence: 77%
See 1 more Smart Citation
“…1A, and 2, A and B). These are molecular mass reported previously for the two proteins (Szatmari et al, 2006;Huang et al, 2009). We observed some interindividual differences in BCRP and to a lesser extent PPAR␣ expression in BBB-ECs (Fig.…”
Section: Expression Of Bcrp and Ppar␣ Proteins In Hcmec/d3supporting
confidence: 77%
“…The final concentration of siRNA and Lipofectamine added to the cells were 100 nM and 2 l/ml, respectively. Cells were cultured in the presence of transfection mixture for 24 h, as described previously (Huang et al, 2009). The following day, transfection mixture was replaced by fresh …”
Section: Methodsmentioning
confidence: 99%
“…The endothelial cells of the capillaries in CNS form tight junctions with low permeability, which contributes to the protective function of BBB (29). The integrity of the tight junction directly determines the permeability of BBB (30). With Western blot analysis, we observed that upon LTD 4 treatment for 24-36 h, the tight junction protein ZO-1 was significantly reduced in bEnd.3 cells (Fig.…”
Section: Montelukast Alleviates Ltd 4 -Induced Bbb Disruptionmentioning
confidence: 84%
“…Studies using a murine preadipocytes cell line showed that HIV-1 Vpr suppressed PPARg-mediated gene transcription, which may contribute to viral-induced dysregulation of metabolic function (39). Overexpression of PPAR-a and PPAR-g attenuated HIVinduced down-regulation of TJ proteins ZO-1, occludin, and junctional adhesion molecules in brain endothelial cell lines (40), and protected against HIV-and Tat-induced expression of inflammatory cytokines and chemokines in macrophages, PBMC, and brain endothelial cells (13,14).…”
Section: Discussionmentioning
confidence: 99%